Well of Ascension - Sanderson, Brandon (New York Tor, 2008)
Vin, the former street urchin and protege of Kelsier, is now heir to the Mistborn and the new world Kelsier created. When a mad race of giants attempt to take the former capital, Luthadel, Vin and her rebel allies must save the city and its hidden cache of allomancy metals from siege.
"A Tom Doherty Associates book."
Reprint. Originally published; New York : Tor, 2007.
Keywords: Courts and courtiers; Sieges; Fantasy fiction; Fiction